CSA bundle 2 integrated aquaculture agriculture system: promoting integrated aquaculture agriculture system through on-farm demonstration and use of socio-cultural innovations to disseminate climate information - HopeWays Enterprises Limited (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
HopeWays Enterprises seeks to enhance dissemination of CIS/CSA technologies through social and cultural innovations using various locally available communications technologies and other methods suggested by the AICCRA project. The proposed project will also increase production of quality fingerlings using climate smart technologies such the greenhouse and other technologies developed by international agriculture research centers; and promote production and marketing of farmed fish using land based integrated agriculture system. We aim to do our work in Luapula and Northern provinces of Zambia where aquaculture is highly affected by climate-related extreme weather events such as floods and unpredictable rainfall patterns. Climatic hazards ‘have adversely impacted food and water security, water quality, and livelihoods of the people, especially in rural communities’ dependent more on aquatic food systems. Luapula and Northern provinces are among the poorest provinces in Zambia, with 80.5% of people in the two provinces classified as poor and 64.5 % classified as extremely poor as of 2010 (CSO, 2010:2). The poorest people are vulnerable to extreme climate events. In 2018, 9615 smallholder fish farmers were identified, 45% of whom are in the Northern and Luapula provinces of Zambia (MF&L, 2019:25-29).